The Effect of The Head Master of Principal's Democratic Leadership Style on Motivation of Teacher Work in State of Madrasah Aliyah, Tapaktuan - Muhsin Muhsin (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
Democratic leaders always try to stimulate their members to work cooperatively to achieve common goals. Democratic leadership places humans as the main and most important factor in each group / organization. The aim is To improve employee performance, efforts are needed to arouse employee motivation and other factors that influence it. this study is a quantitative approach is one of the efforts of scientific search (scientific inquiry) which is based on logical positivism philosophy about logic, truth, laws, and predictions (Watson in Danim). The results are the study show that there is an influence of the principal's democratic leadership style on teacher work motivation in the Tapaktuan Superior State Madrasah Aliyah.